An integrated process for xylooligosaccharide and bioethanol production from corncob. (May 2018) - Boonchuay, Pinpanit; Techapun, Charin; Leksawasdi, Noppol; Seesuriyachan, Phisit; Hanmoungjai, Prasert; Watanabe, Masanori; Takenaka, Shinji; Chaiyaso, Thanongsak
Graphical abstract: Highlights: The corncob was valorized to produce xylooligosaccharide (XO) and bioethanol. XOs with a high xylobiose (X2) content were produced by an in-house endo-xylanase. Bioethanol production was achieved by using a new thermotolerant yeast. This process generated 115 g of XOs and 145 g of ethanol from 1 kg of corncob. Abstract: An integrated process for xylooligosaccharides (XOs) and bioethanol production from corncob was investigated. XOs were produced by a consecutive process of KOH treatment and hydrolysis by an in-house thermostable endo -xylanase from Streptomyces thermovulgaris . XO yields of 0.15 g/gKOH-treated corncob (22.13 g/L) and 0.52 g/graw corncob of cellulose-rich corncob (CRC) were obtained. After 96 h of enzymatic hydrolysis, CRC hydrolysate contained 62.16, 51.21, 10.03 and 0.92 g/L of total sugar, glucose, xylose and arabinose, respectively. Bioethanol production by separate hydrolysis and fermentation (SHF) using CRC hydrolysate, and by simultaneous saccharification and fermentation (SSF) using CRC was studied at 40 °C for thermotolerant Candida glabrata . SHF showed an ethanol yield of 0.28 g/gCRC (21.92 g/L) and ethanol productivity of 0.304 g/L/h with 93% theoretical yield. Surprisingly, by SSF, those parameters were 0.27 g/gCRC (31.32 g/L), 0.33 g/L/h and 89%, respectively. This integrated process might be a new cost-effective approach for corncob valorization.